Building a Safe Islamic Boarding School Environment from Bullying: The Role of Islamic Education in Supervision and Internalization of Values - Nasirudin Nasirudin; Sudjai Sudjai; Novita Siswayanti; Mohamad Miftah; Nasikhin Nasikhin (Nazhruna: Jurnal Pendidikan Islam, 2026)
This study examines how Al-Irsyad Islamic Boarding School in Semarang Regency handles bullying through Islamic teachings, focusing on supervision and the internalization of values. The researchers collected data using a qualitative case study design through in-depth observations, interviews, and documentation. They analyzed the data based on Creswell's qualitative data analysis model. The study identifies two forms of bullying: verbal and social bullying. Verbal bullying typically involves demeaning remarks, such as teasing or assigning negative nicknames. Students often trigger this behavior through careless actions or rule violations. Verbal bullying also includes body shaming, such as calling someone bald. Meanwhile, social bullying generally occurs when students perceive certain actions as harmful to individuals or groups. In response, students may exclude others socially or limit interactions as a form of informal social sanction within group dynamics. Promotive, preventive, and rehabilitative strategies play a crucial role in creating a bullying-free environment. Promotive activities aim to instill moral values in students by emphasizing that bullying is wrong and highlighting the importance of compassion. Educators implement this strategy through initiatives such as banner displays, seminars, and lectures. Preventive measures use technology, such as CCTV, to enhance security, and rely on human supervision through coaching and mentoring systems. Curative measures focus on guiding perpetrators of bullying and preventing the recurrence of negative behavior.